MENINGKATKAN LITERASI MEMBACA AL-QUR’AN DENGAN METODE SIMA’I - Makhrus Ali, M.; Romadhona, Silvia; Nafisah, Aisatun (As-Sulthan Journal of Education, 2025)
Some factors that can help improve student achievement in learning include teacher professionalism as well as motivation to memorize the Koran. The Qur'an is considered the main guideline in Islam, so every member of the Muslims is obliged to read the Qur'an attentively, in accordance with the rules of tajwid science. The background of this study is due to lack of Qur'anic reading skills in Muhammadiyah primary school students in Pendil Village, Gending Subdistrict, Probolinggo Regency. This study aims to evaluate two main aspects. First, to assess the factual condition of Qur'anic reading skills in Muhammadiyah 2 Pendil primary school students. Second, to observe the application of simai method as a strategy to improve Qur'anic reading skills in Muhammadiyah 2 Pendil primary school students. Third, to examine the impact of the use of simai method in improving Qur'anic reading skills in Muhammadiyah 2 Pendil primary school students. In this study, it used Class Action Research (PTK). Based on the findings of the study, it was revealed that there was an increase in Qur'anic reading literacy in students when applying the Sima'i Method from Pre cycle to cycle I and final evaluation. During the cycle, the average literacy of students reading the Qur'an reaches 70%, still in the low category. However, in the first cycle, there was an increase in student achievement with the average reaching 80% for the full type. The subjects of this study were Qur'anic teachers and students of Muhammadiyah 2 Pendil Elementary School. The interview method is used to record conversations or answers from informants whether from Quranic teachers, coordinators, students or principals